The spheres multibookkeeping as a management accounting record system, generation 2021 - Lozano Núñez, Carlos (2021)
Objective: To analyze the evolution of accounting bookkeeping and propose a management accounting record report denominated multi-bookkeeping sphere of generation 2021. Method: The method used was the descriptive and non-experimental research. In which a series of research articles, congress memory publications and countable events were analyzed. In addition, a sample of 100 people’s opinions, regarding their experience shopping in a company, was also considered for the research. Results: The double bookkeeping sphere is a cold, mechanic, traditional and routine register system; it has been kept in force for more than 500 years, it presents limitations as are the managerial countable measurement, registration and decision making process. The proposed multi-bookkeeping spheres’ report presents components of triple, quadruple, quintuple to infinity bookkeeping’s spheres as systems of accounting records composed by "n" dimensions of qualitative and quantitative variables, which are also internal or external and affect the company. These are rated and counted either in a positive or negative form, and expressed in various indicators to measure the events and the countable facts of the business’ environment. Also, they are built and adapted by constructs managed by the public accountant. Conclusion: The report of multi-bookkeeping spheres as the managerial accounting record of generation 2021, allows measuring the internal or external quantitative and qualitative variables that affect the company, and requires the public accountant’s competences.